Potassium deficiency triggers the development of dormant cells (akinetes) in Aphanizomenon ovalisporum (Nostocales, Cyanoprokaryota)(1) - Sukenik, Assaf (Journal of phycology, 2013)
© 2013 Phycological Society of America.